Enhancement of bending fatigue life in TiNi shape-memory alloy tape by nitrogen ion implantation - Takeda, K.; Matsui, R.; Tobushi, H.; Homma, S.; Levintant-Zayonts, N.; Kucharski, S. (Archives of Mechanics, 2015)
A shape-memory alloy (SMA) is expected to be applied as intelligent or smart material since it shows the functional characteristics of the shape memory effect and superelasticity. Most SMA elements, with these characteristics, perform cyclic motions. In these cases, the fatigue property of SMA is one of the most important issues in view of evaluating functional characteristics of SMA elements. The fatigue properties are complex since they depend on stress, strain, temperature and their hysteresis. If an SMA is implanted with high-energy ions, the thermomechanical properties of the material may change, resulting in long fatigue life. In the present study, the nitrogen ion implantation was applied to modify the surface of a TiNi SMA tape and the influence of implantation treatment on the bending fatigue properties was investigated.